Fiqh Muamalah Drugs in Shari’ah Perspective - Maisyarah Salsabilaa; Asmuni; Andri Soemitra (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
Recently, there have been pros and cons about using one of the vaccines, namely the Measle-Rubella vaccine. The results of the examination carried out by LPPOM MUI, this vaccine was positive for containing pork. One of the fatwas regarding halal certification is fatwa number 02 of 2021 concerning Covid-19 Vaccine Products from Sinovac Life Sciences CO.LTD. China and PT. Bio Farma (Persero). This current study will group the topics of fiqh muamalah research on drugs to find out the existing research map. By using qualitative research with analysis content and focus discussion groups with economists, the articles used are 17 articles published in journals in Indonesia from 2018 to 2021, the topic of this muamalah fiqh research consists of 4 topics, namely 1) Maqasid shariah against MUI Fatwa Number 02 of 2021, MUI Fatwa Number 33 of 2018, and MUI Fatwa No. 04 of 2016; 2) Public perception of the use of the measles rubella vaccine; 3) The use of vaccines as an alternative treatment in the perspective of sharia law; and 4) Health services in an Islamic perspective. Some topics that are suggested for further research include further deepening or collecting DSN fatwas related to the use of vaccines. Keywords: Muamalah Fiqh, Medicine, Sharia, Halal